2017
DOI: 10.1007/s00170-017-0212-6
|View full text |Cite
|
Sign up to set email alerts
|

Robotic manipulation for the shoe-packaging process

Abstract: This paper presents the integration of a robotic system in a humancentered environment, as it can be found in the shoe manufacturing industry. Fashion footwear is nowadays mainly handcrafted due to the big amount of small production tasks. Therefore, the introduction of intelligent robotic systems in this industry may contribute to automate and improve the manual production steps, such us polishing, cleaning, packaging and visual inspection. Due to the high complexity of the manual tasks in shoe production, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Integration of robotic system into a human-centred operation such as the shoe production process presented by Gracia et al brought typical manufacturing challenges into focus; large number of variants, short production runs, complex manufacturing process, manual quality verification, packaging. The applied architecture presented included hardware, software, motion planning, collision, object detection and force control (Gracia et al , 2017). Michalos et al demonstrated in a case study, how complicate it is to upgrade an existing robot to engage in human–robot collaboration.…”
Section: Methodsmentioning
confidence: 99%
“…Integration of robotic system into a human-centred operation such as the shoe production process presented by Gracia et al brought typical manufacturing challenges into focus; large number of variants, short production runs, complex manufacturing process, manual quality verification, packaging. The applied architecture presented included hardware, software, motion planning, collision, object detection and force control (Gracia et al , 2017). Michalos et al demonstrated in a case study, how complicate it is to upgrade an existing robot to engage in human–robot collaboration.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, it is difficult or impossible to devise exact procedures and rule-based action execution schemes in advance. One example here could be to formulate the task to have a robot pack a pair of shoes in a shoebox [85]. Even a task that sounds as simple as this proved to be impossible to be completely modeled.…”
Section: Learning From Humansmentioning
confidence: 99%
“…The use of AR is becoming widespread in the manufacturing sector, for a multitude of reasons. Most common AR technologies include AR markers [51], displays and hologram technologies [52], mobile devices [53], tracking technologies [54], and interaction technologies [55]. AR is revolutionizing the manufacturing industry by offering better insights for product development, equipment maintenance, workforce training, production floor issues, process flow, complex assembly, expert support, quality assurance, and automation [56,57].…”
Section: Augmented Realitymentioning
confidence: 99%